Defense Modeling and Simulation Office Data and Repositories Technology Working Group (DRTWG) meetings held February 7-10, 1995, and additional task force and subgroup meetings held between July 1994 and February 1995 / edited by Iris M. Kameny. - Kameny, Iris, 1932- (Conference proceedings (Rand Corporation), 1995)
This document contains the notes from the Defense Modeling and Simulation Office (DMSO) Data and Repositories Technology Working Group (DRTWG) meeting and related Task Force meetings held at the Institute for Defense Analyses in February 1995. It also contains notes for DRTWG Task Force and Subgroup meetings held between the previous Information/Database Technical Working Group meetings during the week of July 11-15, 1994 and the DRTWG meetings in February. The work was performed for the DMSO as part of its initiative to strengthen the use of modeling and simulation (M & S) throughout the Department of Defense. The main and continuing purpose of the DRTWG is to enable data providers to provide the M & S community with cost-effective, timely, verified, and valid data to promote reuse and sharing of data, interoperability of models and simulations, and improved credibility of modeling and simulation. In addition, the DRTWG addresses the data needs not being met by the DoD Corporate Information Management (CIM) initiative. The document describes DRTWG's continuing efforts to monitor DoD CIM activities and to help DMSO develop compatible modeling and simulation guidelines and procedures whenever possible.